POTENTIAL URBAN DEVELOPMENT PARAMETERS THAT REDUCE ENERGY CONSUMPTION IN RESIDENTIAL AREA - Permana, Ariva Sugandi; Abd. Aziz, Norsiah; Jaffar, Abdul Razak (PLANNING MALAYSIA, 2013)
Cities are relatively the larger energy consumers in comparison to its rural counterparts. Reducing energy consumption in cities through various controlling strategies has significant impact on the conservation of natural resources and environment. Residential density and floor area to land ratio has been used as key parameters in development control tools towards creating harmonious urban development. However no attempt has been made to employ them to lower residential energy consumption. This study attempts to demonstrate the possibility of using residential density and floor area to land ratio as passive parameters to reduce non-transportation energy consumption at household level. The analysis was based on questionnaire survey of nontransportation energy consumption viz. energy for lighting, thermal comfort and cooking purposes at household level in Bandung City, Indonesia. The result shows that non-transportation energy consumption perceptibly associates with the two parameters of development control with a u-shape pattern i.e. the correlation has one lowest point with higher trends at both ends. This finding is important for urban planners in formulating strategies towards lower consumption of non-transportation energy in tropical cities and consequently contributing to better-off urban environment.